SPILLOVER VOLATILITAS HARGA MINYAK DUNIA PADA PASAR MODAL INDONESIA PERIODE TAHUN 2017-2022 - Tyas Danarti Hascaryani; Adam Zain (Contemporary Studies in Economic, Finance and Banking, 2023)
World crude oil prices as represented by Brent Crude and West Texas Intermediate (WTI) have decreased in line with the decline in the Indonesia Composite Index (ICI) during the Covid-19 outbreak. Many countries implemented lockdown policies during the Covid-19 period, thereby hampering the pace of Indonesia's economy as a crude oil importing country. Therefore, this study aims to explain the difference in volatility spillover from world crude oil in ICI "before" and "during" the Covid-19 crisis. This study uses ARIMAX-GARCH as a tool to obtain results from the volatility spillover of world oil prices on the Indonesian capital market in 2017-2022. Furthermore, the use of ARIMAX-GARCH in this study resulted in findings of differences in crude oil spillover in ICI in the "before" and "during" Covid-19 periods. The results before Covid-19 show that there is a negative spillover from world oil price volatility on ICI volatility. Meanwhile, when Covid-19 showed that world oil volatility did not denote spillovers to ICI volatility. This shows a change in the perspective of investors towards crude oil as a consideration for investing in the stock market in Indonesia.